ENHANCEMENT OF SOLUBILITY AND DISSOLUTION OF IBUPROFEN BY SOLID DISPERSION TECHNIQUE AND FORMULATION OF SUSTAINED RELEASE TABLETS CONTAINING THE OPTIMISED BATCH OF SOLID DISPERSION - KAR, ABHIK; AHMED, ABDUL BAQUEE (International Journal of Current Pharmaceutical Research, 2017)
Objective: The present study was aimed to enhance the solubility of poorly water soluble drug Ibuprofen using solid dispersion technique and to develop sustained release tablets containing solid dispersion granules of the optimized batch. Ibuprofen is a non-steroidal anti-inflammatory drug (NSAID) with analgesic, antipyretic, andÂ anti-inflammatory properties Methods: Solid dispersions of Ibuprofen were prepared by using PEG 20000 and Poloxamer 407 in different weight ratios by fusion and solvent evaporation method. Drug-carrier physical mixtures were also prepared. Solid dispersions were characterized by saturation solubility, drug content, in vitro dissolution, FTIR and DSC analysis. Solid dispersion formulation, SDF9 (PEG 20000 and Poloxamer 407, 1:3:3) prepared by solvent evaporation method was considered as the optimized batch. Sustained release tablets containing the solid dispersion granules of the optimized batch were prepared by direct compression method using HPMC K100M at three concentrations (10%, 14%, 18% w/w). The prepared formulations were evaluated for hardness, thickness, weight variation, friability, in vitro dissolution studies and release kinetics modelling. Results: Solid dispersion formulation, SDF9showed 95.09% drug release in 60 min and considered as the optimized batch. Tablet formulation, FT3 (HPMC K100M 18% w/w) showed 96% drug release for 12 h. Conclusion: Solid dispersions of ibuprofen using a combination of PEG 20000 and poloxamer 407 by solvent evaporation method may result in higher aqueous solubility of the drug. Also sustained release tablets containing solid dispersion granules of ibuprofen, using HPMC K100M may be a promising approach to extend the release rate of the drug from the solid dispersion for 12 h.